IMAGE OF VICTORIAN WOMEN IN AN IDEAL HUSBAND DRAMA SCRIPT BY OSCAR WILDE: A FEMINIST READING - Rahayu, Milda; Rasiah, Rasiah; Putra, Ansor (Seshiski: Southeast Journal of Language and Literary Studies, 2024)
This study purposed to show the image of Victorian women in England through the playwright script An Ideal Husband written by Oscar Wilde. Feminist criticism proposed by Elaine Showalter is used as a tool to analyze the women images in the drama script, particularly dealing with Victorian women. The result of the analysis indicated that the script presents women in two faces; women as angels and women as demons. A woman as an angel is described as an ideal image of a woman in Victorian society. They are portrayed as women who maintain piety, purity, submission, and domesticity in societal life. Whereas Women as demon is described as the opposite ones, a contradicting image against the values of traditional Victorian women. They have an aggressive, independent and ambitious attitude which were prohibited to be owned by women. Angel seems represented the ideal image of women in patriarchal norms. Demon, in the other hand, is the picturesque of ideal women in feminist perspective.